Effect of Diabetes Mellitus on Hearing (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Diabetes mellitus (DM) is a chronic systemic disease characterized by hyperglycemia due to absolute or relative deficiency of insulin and affects several systems including hearing. It was evidenced that hearing loss is twice as common in people with diabetes in comparison to other non-diabetic individuals. Although there is no epidemiological information are available in Bangladesh, but it can assume that the number would not be less.Methods: This study was a hospital based case-control study conducted at department of ENT & department of Endocrinology for 1.5 year following approval of the protocol. Total 110 people (55 cases and 55 controls) were selected and analysed in this study. All the patients were divided into two groups: Group A (all patients with Diabetes) and Group B (persons without diabetes). For analysis group A were considered as case and group B were as control. Written informed consent was taken from all case and control subjects. A detailed history taking including hearing loss, duration, onset, associated symptoms & diabetes duration, treatment were obtained from the subject. A detailed ENT examination including otoscopic examination and tuning fork test were also conducted for each patient. Moreover, audiometric assessment-PTA, blood investigation-RBS, HbA1C, & renal parameters like blood urea & serum creatinine were tested in each cases. Data analysis was done in the statistical program Statistical Package for Social Science (SPSS) version 16.0.Results: Out of total 55 patients in each group, mean age of Diabetic and non-diabetic were 46.78±8.02 SD and 46.72±8.09 SD (years) with slight female predominance (45.5% vs 54.5% in diabetic group and 49.1% vs 50.9% in non-diabetic group).Bangladesh J Otorhinolaryngol; October 2019; 25(2): 116-124